A microfluidic paper-based analytical device for early diagnosis and prognosis of acute myocardial infarction / Lim Wei Yin - Lim , Wei Yin (2020)
Acute myocardial infarction (AMI), also termed as heart attack, is often clinically screened by blood test through the measurement of cardiac biomarkers (i.e., troponin (T or I), creatine kinase (CK−MB) and myoglobin) and electrocardiography (ECG) changes which are presented to the hospital. However, the early diagnosis of AMI is challenging because the detection of biomarkers such as troponin (T or I) and CK−MB are only reliable at the intermediate and later stages (> 6 hours after chest pain onset), during myocardial injury and myocardial infarction. On the other hand, myoglobin often been used as early biomarker which is detectable within the first 3 hours of chest pain onset was found to be more specific to skeletal muscle injury rather than myocardial injury. To overcome these limitations, the detection of a new combination of cardiac biomarkers for early diagnosis and prognosis of AMI was demonstrated in this Ph.D. project. The uniqueness of this new combination of cardiac biomarkers detection was to allow an early diagnosis of the patient at risk, to provide immediate therapy and reduce mortality rate of AMI. Glycogen phosphorylase isoenzyme BB (GPBB) was detected as a potential early biomarker of ischemic myocardial injury (within the first 4 hours) while cTnT and CK−MB were detected as prognosis biomarkers of myocardial injury and myocardial infarction. The main objective of this Ph.D. project is to develop a sensitive, low-cost and disposable microfluidic paper-based device (μPAD) for simultaneous detection of multiple cardiac biomarkers utilising both colourimetric and Surface Enhanced Raman Scattering (SERS) detection techniques. The fabricated μPAD was designed with three reaction zones: G for GPBB; M for CK−MB and T for cTnT, which was connected to a central sample zone on a nitrocellulose membrane by wax-printing technique using a wax printer—Fuji Xerox ColorQube 8870. Three different colour nanoparticles (silver, gold urchin and gold) were used as detecting indicator for a particular target analyte. The colourimetric signal could be easily observed easily through the naked eye based on the appearance of the distinct colour. Whereas the SERS signals are measured by the peak characteristics of the respective Raman reporter molecules in SERS probe at the three respective reaction zones. On the other hand, smartphone-based camera and desktop scanner were used as a diagnostic tool in colourimetric quantification; whereas Renishaw InVia Raman Microscope was used in SERS. As for the obtained results, the colourimetric and SERS-based sandwich immunoassay performed on the μPAD showed good reproducibility (RSD approximately 10%), good intra- and inter-day precision (CV 10%–20%), consistent stability test results throughout the 28 days, and a strong correlation between these three developed diagnostic tools ─ smartphone–based camera (R2 = 0.96); desktop scanner (R2 = 0.94) and SERS (R2 = 0.97) with the laboratory Siemens Centaur XPT Immunoassay System (a laboratory method) used at University Malaya Medical Center (UMMC). Additionally, to omit the requirement of the calibration curve for quantitative measurement, partial least squares (PLS) models were designed to quantify the levels of cardiac biomarkers with the Raman spectral data, for GPBB assay with R2 = 0.94; CK-MB assay with R2 = 0.80; and cTnT assay with R2 = 0.86. This method allows for absolute quantitative measurement when the conventional calibration curve fails to provide accurate estimate of the cardiac biomarkers, especially at low and high concentration ranges. Overall, the present findings indicated the potential of μPAD platform as a point-of-care testing (POCT) device for early diagnosis and prognosis of AMI by using smartphone-based camera/desktop scanner and Raman spectroscopy as a diagnostic tool for colourimetric detection and SERS detection, respectively. Hence, this developed the μPAD with a new combination of cardiac biomarkers which potentially function as a POC device for prompt diagnosis by rapid exclusion of MI (quantified by using a calibration curve or a calibration- free predictive diagnostic model).